A diversidade de lagartos na Caatinga é mediada pelos térmitas? - Souza, Heitor Bruno de Araujo (2012)
Intending to explain the extraordinary lizard coexistence levels found in Australian deserts, Morton & James (1988) figured out a hypothesis which defends that the termite diversity would bring about lizard radiation. This study aims to verify the validation of that hypothesis in Caatinga lizard assemblages. This study also objectives verifying if the termite defense mechanisms influence their consuming levels by lizards and if this pattern differs between different lizard lineages. Termites were collected using a standardized sampling protocol of termites. Besides using haphazard sampling, we collect lizards with 108 pitfall traps in each area. Intending to check the linkage between the termite and lizard assemblages, the lizard stomach contents were analyzed and then a canonical correspondence analysis was performed. The presence of nonrandom patterns of diet overlap among the lizard species was also examined. Aiming to check if the defense mechanisms of termite influence their consuming pattern by lizards it was performed a laboratory experiment where termite with different defense mechanisms were offered to lizards of two different lineages. We verified that lizard assemblages do not consume termites according to termite abundance in ecosystems. Furthermore, mean niche overlap lizard species did not differ significantly from that expected by chance. We found that termite chemical defense mechanism does influence the termite s pattern consuming by lizards. These results do not corroborate premises which support Morton & James hypothesis (1988) and point out that lizard do not chose termites based on their abundance, but, trying to avoid consuming termites which exhibit chemical defense mechanisms. This defense mechanism, however, may not be the only explanation to patterns of termite s consuming by lizards.